1999
DOI: 10.1038/sj.bjc.6690372
|View full text |Cite
|
Sign up to set email alerts
|

Granisetron compared with prednisolone plus metopimazine as anti-emetic prophylaxis during multiple cycles of moderately emetogenic chemotherapy

Abstract: Summary This randomized, double-blind, double-dummy parallel study compared the anti-emetic efficacy and tolerability of the serotonin antagonist granisetron with prednisolone plus the dopamine D 2 antagonist metopimazine during nine cycles of moderately emetogenic chemotherapy. Chemotherapy naive women with stage I or II breast cancer scheduled to intravenous cyclophosphamide, fluorouracil and methotrexate or cyclophosphamide, epirubicin and fluorouracil every 3 weeks were included. Patients received a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…[25][26][27] This differs from the patients who received CHOP/FAC regimens, who were likely to be female patients with breast cancer who had a high propensity for nausea and emesis (that is, young and female with low alcohol consumption). 20 Some subsequent studies have compared the efficacy of 5-HT 3 receptor antagonists with older, conventional antiemetics and found that women were protected significantly better from acute nausea and emesis with granisetron 28 or ondansetron, 29 weakening the hypothesis that antiemetic regimens should be determined solely by the predicted emetogenicity of the chemotherapy agents received. Rather, a major consideration for all consulting physicians ought to be individual patient characteristics.…”
Section: Patient Susceptibilitymentioning
confidence: 99%
“…[25][26][27] This differs from the patients who received CHOP/FAC regimens, who were likely to be female patients with breast cancer who had a high propensity for nausea and emesis (that is, young and female with low alcohol consumption). 20 Some subsequent studies have compared the efficacy of 5-HT 3 receptor antagonists with older, conventional antiemetics and found that women were protected significantly better from acute nausea and emesis with granisetron 28 or ondansetron, 29 weakening the hypothesis that antiemetic regimens should be determined solely by the predicted emetogenicity of the chemotherapy agents received. Rather, a major consideration for all consulting physicians ought to be individual patient characteristics.…”
Section: Patient Susceptibilitymentioning
confidence: 99%
“…As described in the previous guidelines [2, 12], dexamethasone has been consistently equal or superior to metoclopramide and equal to 5-HT 3 -receptor antagonists such as ondansetron [21] and granisetron [19] in patients receiving cyclophosphamide-or anthracycline-based chemotherapy. Two randomized studies have indicated that dexamethasone plus prochlorperazine [31] or prednisolone plus metopimazine [28] is inferior to granisetron in patients receiving MEC. In the first study chemotherapy also included cisplatin (20-50 mg/m 2 ) and in the second study prednisolone was given in a dose equal to only 50% of the recently established optimal dose of dexamethasone [20].…”
Section: Corticosteroidsmentioning
confidence: 98%
“…In the first study 223 patients were followed through nine cycles of CMF/CEF chemotherapy (total number of cycles 898). Neither granisetron alone nor prednisolone plus metopimazine was able to maintain antiemetic efficacy [28]. These antiemetic regimens are, however, no longer recommended as a standard for prophylaxis of emesis induced by MEC.…”
Section: Multiple Cycles Of Mecmentioning
confidence: 99%
“…Between 44 and 53% of patients receiving highly emetogenic chemotherapy with cisplatin ≥70 mg/m 2 and preventive treatment with a serotonin antagonist plus dexamethasone experienced delayed CINV (Aguilar et al 2005). There is also evidence that the protective effect of a serotonin antagonist plus a corticosteroid wears off during multiple cycles of chemotherapy (Soukop et al 1992;Sigsgaard et al 1999Sigsgaard et al , 2001). …”
Section: Unmet Needsmentioning
confidence: 99%